Artificial wetlands in the conservation of water resources: An ecocentrism perspective - Fadri, Zainal (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Background: Water pollution is a kind of environmental damage. Water pollution occurs in developing countries and developed countries. The government has made efforts to preserve water resources. However, it has only reached some levels of society because there are still many facilities that are more important than transportation, food security, and the security system. This research sees ecocentrism given the artificial marsh technique as the conservation of water resources as well as highlights equality of the purpose of the artificial marsh technique with the principle proposed ecocentrism about morality against the universe, so the proposed environmental ethics principles that have to be met in the implementation of the artificial marsh technique on sustainable preservation of water resources planning. Method: This research is library research. The research analysis is an analysis of the approach to a concept; the first phase is the interpretation and categorization, the second phase is data classification, the third phase is the analysis of synthesis, and the fourth phase is a critical evaluation by using element methodical as description, verstehen, interpretation, hermeneutic, inductive, and heuristic. Findings: The result shows that human beings have a duty to manage and preserve nature, and man is forbidden to exploit nature. Views ecocentrism is seen in the preservation of water resources as an effort to protect and preserve nature. Conclusion: Human beings are a part of the universe and are obliged to manage and preserve the guard, so the artificial marsh technique can be used in planning to preserve sustainable water resources. Novelty/Originality of this study: This research could lead to a new model for engaging communities in water conservation projects emphasizing the ethical relationship between humans and nature. This model could include educational programs and practical activities that help communities understand and apply the principles of ecocentrism in their daily lives.